Accuracy of Information Maintained by US Credit Bureaus: Frequency of Errors and Effects on Consumers' Credit Scores. Issue 3 (9th October 2013) - SMITH, L. DOUGLAS; STATEN, MICHAEL; EYSSELL, THOMAS; KARIG, MAUREEN; FREEBORN, BETH A.; GOLDEN, ANDREA
<x xml:space="preserve">Abstract</x> A representative sample of 1, 000 US consumers reviewed their credit reports from the three major US credit bureaus with help from university research associates. Twenty‐six percent of study participants claimed to find at least one potentially material error and filed formal disputes with the relevant bureau(s). For 78% of the 263 consumers who filed disputes (20% of participants overall) at least one bureau altered the credit report accordingly. Thirty‐three percent of disputants (8.7% of participants) experienced a resulting increase of 10+ points in one or more of their FICO® scores; 21% of disputants (5.5% of study participants) had one or more scores cross a threshold that would typically result in more favorable terms of credit. Our findings suggest that credit‐bureau data are accurate enough to facilitate efficient lending and creditors' management of accounts, but individual consumers need to be vigilant to protect themselves against potentially costly errors in their files.